INVESTIGATION OF ANTIDIABETIC ACTIVITY OF AERIAL PARTS OF WALSURA PISCIDIA ROXB IN HIGH FAT DIET (HFD) FED – STREPTOZOTOCIN (STZ) INDUCED DIABETIC RATS - I. SARATH CHANDIRAN,; K. B. CHANDRA SEKHAR,; DEEPAK KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
The present study was aimed to evaluate the antidiabetic activity of ethanolic extract of aerial parts Walsura piscidia Roxb (EEWP) on high fat diet (HFD) - Streptozotocin (STZ) induced diabetic rats. Male wistar albino rates were fed with high fat diet for a period of two week prior to administration of Streptozotocin 50mg/kg intrapeitonially. The long duration effect of the extract was investigated by treating diabetic rats with vehicle (0.5%mg/kg) EEWP (200 and 400mg/kg body wt) for the period of 28 days. The results of EEWP on fasting blood glucose and serum insulin levels were evaluated. In addition of body weight changes, lipid profile and serum biomarkers of liver and kidney utility were also studied. The results raise the roof that EEWP-400mg shows admirable anti-diabetic activity. The elevated serum urea and creatinine level decreased by treatment with the extract. Thus the results defend Walsura piscidia Roxb (EEWP) acquire an antidiabetic activity.